Conformable derivative applied to experimental Newton’s law of cooling - J. Rosales-García (Revista Mexicana de Física, 2020)
It has been proved that the integer order differential equation does not represent the real behaviour of nature for Newton’s law of cooling. Then, we solve Newton’s cooling law using the conformable derivative; as a result, we obtain the Kohlrausch stretched exponential function. Due to the free parameter 0 < γ ≤ 1, we can fit this function with the graph of the experimental data set. It is shown that the experimental data coincide with those theoretical when γ = 0.77269 and k = 0.018765.